Disruption of Long-Term Alcohol-Related Memory Reconsolidation: Role of β-Adrenoceptors and NMDA Receptors - Wouda, Jelte A.; Diergaarde, Leontien; Riga, Danai; Van Mourik, Yvar; Schoffelmeer, Anton N.; De Vries, Taco J. (Frontiers in Behavioral Neuroscience, 2010)
Disrupting reconsolidation of drug-related memories may be effective in reducing the incidence of relapse. In the current study we examine whether alcohol- related memories are prone to disruption by the β -adrenergicreceptor antagonist propranolol (10 mg/kg) and the NMDA receptor antagonist MK801 (0.1 mg/kg) following their reactivation. In operant chambers, male Wistar rats were trained to self-administer a 12% alcohol solution. After 3 weeks of abstinence, the animals were placed in the self-administration cages and were reexposed to the alcohol-associated cues for a 20-min retrieval period, immediately followed by a systemic injection of either propranolol, MK801 or saline. Rats were tested for cue-induced alcohol seeking on the following day. Retrieval session, injection and test were repeated on 2 further occasions at weekly intervals. Both propranolol and MK801 administration upon reactivation did not reduce alcohol seeking after the first reactivation test. However, a significant reduction of alcohol seeking was observed over three post-training tests in propranolol treated animals, and MK801 treated animals showed a strong tendency towards reduced alcohol seeking (p=0.06). Our data indicate that reconsolidation of alcohol-related memories can be disrupted after a long post-training interval and that particularly β-adrenergic receptors may represent novel targets for pharmacotherapy of alcoholism, in combination with cue-exposure therapies.